Longitudinal association of inflammatory markers with markers of glycaemia and insulin resistance in European children. Issue 3 (16th November 2021) - Nagrani, Rajini; Foraita, Ronja; Wolters, Maike; De Henauw, Stefaan; Marild, Staffan; Molnár, Dénes; Moreno, Luis A.; Russo, Paola; Tornaritis, Michael; Veidebaum, Toomas; Ahrens, Wolfgang; Marron, Manuela; et al.
Abstract: Purpose: Subclinical systemic inflammation may lead to development of type 2 diabetes, but there has been no investigation into its relationship with early progression of glycaemic deterioration and insulin resistance, especially in younger population. In this study we assessed longitudinal associations of pro‐ and anti‐inflammatory markers with markers that evaluate glycaemia and insulin resistance. Methods: This study includes 6537 initially nondiabetic children (mean age at baseline = 6.2 years) with repeated measurements from the IDEFICS/I.Family cohort study (mean follow‐up = 5.3 years) from eight European countries. Markers of inflammation were used as independent variables and markers of glycaemia/insulin resistance as dependent variables. Associations were examined using two‐level growth model. Models were adjusted for sex, age, major lifestyle, metabolic risk factors, early life markers, and other inflammatory markers in final model. Results: Children with 6 years of follow‐up showed that a one‐unit increase in z‐score of leptin level was associated with 0.38 (95% CI = 0.32 to 0.44) unit increase in HOMA‐IR z ‐scores. Leptin continued to be associated with HOMA‐IR even when analysis was limited to children with no overall obesity, no abdominal obesity, and low to normal triglyceride levels. An inverse association was observed between IL‐15 and HOMA‐IR ( β = −0.11, 95% CI = −0.15 to −0.07). Conclusions: IL‐15 should be evaluated further in the prevention or treatment of prediabetes whereas leptin may prove to be useful in early detection of prediabetes via their association with markers of insulin resistance in European children.